Prognostic Value of Combining Apelin-12 and Estimated Glomerular Filtration Rate in Patients with ST-Segment Elevation Myocardial Infarction - Yue Liu; Huasong Xia; Meng Li; Yi Chen; Yanqing Wu (Journal of Interventional Cardiology)
Background. Apelin-12 and estimated glomerular filtration rate (eGFR) are considered prognostic factors for ST-segment elevation myocardial infarction (STEMI). However, little is known about whether the combined use of these two biomarkers could enhance the prognostic value. This study aimed to investigate the utility of combining apelin-12 and eGFR for STEMI. Methods. Patients were divided into four groups based on median apelin-12 level and eGFR level: A: low apelin-12, low eGFR; B: low apelin-12, high eGFR; C: high apelin-12, low eGFR; and D: high apelin-12, high eGFR. The Cox regression was used to identify prognostic factors. The Kaplan–Meier and the receiver operating characteristic (ROC) curves were generated to evaluate the prognostic value of apelin-12 combined with eGFR in patients with STEMI. Results. Among 460 patients, 118 (25.7%) experienced major adverse cardiac events (MACEs) during the entire follow-up of 30 months. The Kaplan–Meier curve analysis revealed that group D had the best prognosis compared with the other three groups. The combination of apelin-12 and eGFR (area under the ROC curve (AUC), 0.699) enhanced the predictive value for MACE compared with either apelin-12 (AUC, 0.617) or eGFR (AUC, 0.596) alone. There was a negative association between apelin-12 and eGFR (r = −0.32, p<0.001), while no association was observed between the Gensini score and apelin-12 or eGFR. Conclusions. This study suggests that both low apelin-12 (<0.76 ng/ml) and low eGFR (<94.06 mL/min/1.73 m2) are associated with poor prognosis in STEMI, indicating that the combination of apelin-12 and eGFR could enhance the prognostic value of patients with STEMI.